Effect of kenaf fiber loading on the mechanical and physical properties of bio-epoxy composites - Odesanya, Kazeem Olabisi; Jawaid, Mohammad; Ismail, Ahmad Safwan; Alothman, Othman Y.; Dhakal, Hom Nath; Abu-Jdayil, Basim (Taylor and Francis, 2026)
Research on sustainable materials has increased in the past decade. This study focuses on investigating the effect of different fiber loading on the physical and mechanical properties of kenaf/bio-epoxy by varying the fiber loading, which is 30, 40, 50, and 60 wt%. The density, water absorption, and thickness swelling of the composite increases as fiber loading increases. The composites were prepared in good condition, where the void content was reported below 4%. In addition, increasing the fiber loading of the samples enhanced their impact strength significantly compared to neat bio-epoxy. However, the tensile and flexural properties of the samples studied did not show a positive enhancement. Scanning Electron Microscopy (SEM) revealed that the kenaf–epoxy composites exhibited high fiber dispersion, greater fiber-matrix wettability, and fiber debonding, which can be used to explain the finding on the mechanical properties. It can be concluded from this research that kenaf/bio-epoxy composites (K-60) have the best overall impact strength compared to other composites.